PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS KARAKTER DALAM PEMBELAJARAN BIOLOGI UNTUK SISWA KELAS X MA - Amelia, Selvi; Haviz, M.; Delfita, Rina (Jurnal Pembelajaran MIPA, 2014)
The purpose of this research is to get a product as LKS biology based on validity and practicality. Observational type that used in this research is Research of Development. Developmental model that used is model 4-D, which is define, design, develop and disseminate. The research procedure is done by three phases which are phase define, design phase and develop phase. Based on the evaluation that have been done is know that students work sheet (LKS) basis character that has been created is valid, through validity testing by some validator. Practicality testing result through questionnaire is categorized it is very practice. Meanwhile, practicality testing trough observation and interview, (LKS) is practis after proces by using descriptive technique. In conclution, the quality of product that is result of research development can be said valid and practice based on result of testing validity and testing practicality that has been done.Key words: Development, LKS, caracter, validity, practicality